Optimising traffic control for a congested intersectton - Rahmat, Riza Atiq; Jumari, K.; Hassan, Azmi; Basri, Hassan (Hemming Group, 2002)
ln congested road networks, a signalised intersection that determines cycle time and green time splits based on current traffic demand will greatly improve traffic flows. Vehicle actuated traffic signals are very commonly used to control isolated intersections due to their ability to respond to the actual traffic demand. However it was observed that unnecessary stop delays occur because the given green time allocations were more than that required. This is due to position of the detector which is located in the vicinity of the stop line. A significant reduction in vehicle delay was observed when the detectors were located 30 - 40 meters from the stop lines. Also, the signal performance was observed to deteriorate when most arms of the junction were congested. The reason for this deterioration was that the pre-set maximum green times were not optimised for the actual traffic demand. ln this study the genetic algorithm technique was utilised to optimise traffic control by minimising a performance index which, in this case, is the stop-delay. ln the event of over congestion, the traffic signal will control the traffic by emulating manual control by traffic marshals by prioritising selected arms or giving more green times based on queue length or a combination of both.